Evaluación de diferentes variedades de oxalis tuberosa (OCA) para la obtención de harina con fines industriales - Martínez Contreras, Karla Geomaira (2015)
In this research the properties of flour oca (Oxalis tuberosa) for use for industrial purposes was evaluated and variety with higher nutritional properties between OCA WHITE AND YELLOW, thus the appropriate method was validated maturation was established oca (sun or heat induced) and determined the days of ripening goose between (3 and 6 days). The sample size per treatment was 500 g, 8 treatments was considered 4 kg goose were used by two repetitions ie 8 kg of the same, these distributed as follows 4kg white goose and 4 kg of yellow goose and the drafting process was to ripen in the sun and heat induced for 3 and 6 days respectively and each treatment being dehydrated for 5 hours on the stove and then be subjected to milling. For the determination of iron and phosphorus in the flour goose was performed by means of laboratory Labolab in Quito and the AOAC 944.02 method for iron and AOAC 986.24 for phosphorus, in addition to these proceeded to evaluate the percentage was used fat, moisture, protein, fiber, ash and energy containing flour goose in food science laboratory State Technical University of Quevedo. In the results of phosphorus factor A (white Oca) (209.72%), factor B: (induced Heat) (202.51%), factor C (6 Days) (200.39) and regarding iron, factor A: (Oca yellow) (34.34%), factor B (induced Heat) (25.31%), factor C: (6 days) (26.87%). It is recommended to consume 45-50 g of flour goose white goose variety matured induced heat for 6 days to cover the daily intake of 14 mg of phosphorus and 700 mg of iron.